2019
DOI: 10.1002/job.2366
|View full text |Cite
|
Sign up to set email alerts
|

Predicting retail shrink from performance pressure, ethical leader behavior, and store‐level incivility

Abstract: Summary Retail shrink, a form of inventory loss due primarily to employee theft and shoplifting, is a growing concern for retailers. Prior work on shrink has taken primarily an individual‐level focus to understanding this problem but has yet to really explore how the business context impacts shrink. The current study addresses this need by delineating and testing a unit‐level (i.e., between‐stores) conceptual model, wherein we examine the influence of performance pressure, ethical leader behavior, and store‐le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 105 publications
1
26
0
Order By: Relevance
“…work pressure, performance pressure) as threatening may feel stress (Casper and Sonnentag, 2019) and may concentrate on the difficulties of raising performance and the adverse consequences that will likely result if performance demands are not met (Mitchell et al, 2019). These perceptions could also lead employees to experience negative outcomes such as job dissatisfaction (Quratulain and Khan, 2015), deviant behavior (Jensen et al, 2019;Soomro et al, 2020) and low job involvement (Sonnentag and Kruel, 2006) if performance is not raised. However, we lack empirical evidence on whether performance pressure impacts employee work engagement through threat appraisal.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…work pressure, performance pressure) as threatening may feel stress (Casper and Sonnentag, 2019) and may concentrate on the difficulties of raising performance and the adverse consequences that will likely result if performance demands are not met (Mitchell et al, 2019). These perceptions could also lead employees to experience negative outcomes such as job dissatisfaction (Quratulain and Khan, 2015), deviant behavior (Jensen et al, 2019;Soomro et al, 2020) and low job involvement (Sonnentag and Kruel, 2006) if performance is not raised. However, we lack empirical evidence on whether performance pressure impacts employee work engagement through threat appraisal.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…As a result, employee parenthood and organizational parental leave policies moderated the effects of employee gender on experienced incivility, which led, in turn, to the career withdrawal. The last study of this category was conducted by Jensen et al (2019), which focused on performance pressure, ethical leadership, store incivility and store shrink. Accordingly, the performance pressure along with ethical leadership influenced store-level incivility.…”
Section: Theoretical Functions Of Wimentioning
confidence: 99%
“…Research on performance pressure has found that it is a unique and dynamic work stressor which acts as a double-edged sword in that it can motivate employees to perform well (Mitchell et al, 2019), be more ethical (Ness et al, 2017) and creative (Zhang et al, 2017), while also increasing stress (Mitchell et al, 2018) and deviant behavior (Jensen et al, 2019). Mitchell et al (2019) theorized that performance pressure elicits both positive and negative workrelated behaviors which depends on the extent to which individuals appraise the performance pressure as a challenge or a threat.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%